2016
DOI: 10.1097/md.0000000000005633
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and management for pyloric stenosis occurred after endoscopic submucosal dissection adjacent to pylorus

Abstract: Endoscopic submucosal dissection (ESD) has been widely accepted as a curative treatment for gastric neoplasm. Pyloric stenosis is a chronic complication that can be caused by ESD. The aim of this study is to clarify the risk factors and management for pyloric stenosis. From January 2004 to January 2014, a total of 126 patients who underwent ESD adjacent to pylorus were reviewed retrospectively. Pyloric mucosal defect was defined as when any resection margin of ESD was involved in the pyloric ring. Pyloric sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 21 publications
1
37
1
Order By: Relevance
“…Some observational studies indicated that one of the important risk factors for stenosis after gastric ESD in both cardia and pylorus was circumference of resection wound >3/4 …”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
See 3 more Smart Citations
“…Some observational studies indicated that one of the important risk factors for stenosis after gastric ESD in both cardia and pylorus was circumference of resection wound >3/4 …”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
“…Stenosis after gastric ESD is mainly treated by EBD. Two articles reported that there was no perforation related to EBD for cardiac stenosis, whereas perforation that developed during EBD for pyloric stenosis required emergency surgery . Two interesting reports described the usefulness of mucosal incision of stenotic ulcer scar and subsequent steroid injection …”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
See 2 more Smart Citations
“…Pyloric obstruction can also be a result of Bouveret's syndrome [24] and bacterial infection of the gastric wall or gastric wall abscess after cholecystitis [26]. Endoscopic submucosal dissection of the pyloric ring has also been found to be a risk factor for pyloric stenosis [38].…”
Section: Comorbid Conditionsmentioning
confidence: 99%